"Work for what?" the meaning and the sense of work for the bankers - Bertosso, Henrique; Ebert, Paula; Bonemberger, Angela Maria Ortolan; Centenaro, Andressa; Severo, Eliana Andréa (Revista de Administração da UFSM, 2019)
The work of the banking sector has been affected by several transformations, especially by the insertion of the technological equipment in the agencies and integrated information systems, to control the time, the work and the productivity of the bankers. In this context, the purpose of this study is to understand the meaning and meaning of the work for bankers. The research characterized by the quantitative method, and the data collection was carried out through a survey applied to 65 bankers, who answered a questionnaire with closed questions. Data were analyzed using descriptive statistics techniques (mean and standard deviation) and factorial analysis. The main meanings pointed out by the bankers are that the work is something that allows the improvement, that adds value to life, as well as offers a contribution to the community. In this sense, work means a set of relevant activities to meet professional needs, personal values and contribute to society. It was found that the main factors that give meaning to the work in the banking sector is the guarantee of a quiet future, respect in the work environment, transparency and, its influence and social utility in what comprises justice and equality, corresponding to the desires Interests of the worker.